Focusing of Spotlight Tandem-Configuration Bistatic Data with Frequency Scaling Algorithm - Shichao Chen; Ming Liu; Jun Wang; Fugang Lu; Mengdao Xing (International Journal of Antennas and Propagation)
A frequency scaling (FS) imaging algorithm is proposed for spotlight bistatic SAR data processing. Range cell migration correction (RCMC) is realized through phase multiplication. The proposed algorithm is insensitive to the length of the baseline due to the high precision of the point target (PT) spectrum that we are based on. It is capable of handling bistatic SAR data with a large baseline to range ratio. The algorithms suitable for small and high squint angles are both discussed according to whether the range dependence of the second range compression (SRC) can be neglected or not. Simulated experiments validate the effectiveness of the proposed algorithm.